The Lack of the TetR-Like Repressor Gene BCG_2177c (Rv2160A) May Help Mycobacteria Overcome Intracellular Redox Stress and Survive Longer Inside Macrophages When Surrounded by a Lipid Environment - García-Morales, Lázaro; Del Portillo, Patricia; Anzola, Juan M.; Ares, Miguel A.; Helguera-Repetto, Addy C.; Cerna-Cortes, Jorge F.; Méndez-Tenorio, Alfonso; García, María J.; Otal, Isabel; Martín, Carlos; Gonzalez-y-Merchand, Jorge A.; Rivera-Gutiérrez, Sandra (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacteria, like other microorganisms, survive under different environmental variations by expressing an efficient adaptive response, oriented by regulatory elements, such as transcriptional repressors of the TetR family. These repressors in mycobacteria also appear to be related to cholesterol metabolism. In this study, we have evaluated the effect of a fatty acid (oleic–palmitic–stearic)/cholesterol mixture on some phenotypic and genotypic characteristics of a tetR-mutant strain (BCG_2177c mutated gene) of M. bovis BCG, a homologous of Rv2160A of M. tuberculosis. In order to accomplish this, we have analyzed the global gene expression of this strain by RNA-seq and evaluated its neutral-lipid storage capacity and potential to infect macrophages. We have also determined the macrophage response by measuring some pro- and anti-inflammatory cytokine expressions. In comparison with wild-type microorganisms, we showed that the mutation in the BCG_2177c gene did not affect the growth of M. bovis BCG in the presence of lipids but it probably modified the structure/composition of its cell envelope. Compared to with dextrose, an overexpression of the transcriptome of the wild-type and mutant strains was observed when these mycobacteria were cultured in lipids, mainly at the exponential phase. Twelve putative intracellular redox balance maintenance genes and four others coding for putative transcriptional factors (including WhiB6 and three TetR-like) were the main elements repeatedly overexpressed when cultured in the presence of lipids. These genes belonged to the central part of what we called the “genetic lipid signature” for M. bovis BCG. We have also found that all these mycobacteria genotypic changes affected the outcome of BCG-infected macrophages, being the mutant strain most adapted to persist longer inside the host. This high persistence result was also confirmed when mutant-infected macrophages showed overexpression of the anti-inflammatory cytokine TGF-β versus pro-inflammatory cytokines. In summary, the lack of this TetR-like repressor expression, within a lipid environment, may help mycobacteria overcome intracellular redox stress and survive longer inside their host.